Postrzeganie procesu uczenia się języka obcego w perspektywie uczniów dorosłych (badanie jakościowe nauczycieli-konsultantów) - Werbińska, Dorota (Neofilolog, 2019)
The article aims at presenting a longitudinal two-year study on the per-ception of language learning from the perspective of five adult learners in their late 50s who are teacher consultants by profession and participants of an elementary course in English. The attention is focused on two as-pects: 1) what general expectations they have with regard to the course (ie. language skills, knowledge, teacher, etc.) at the beginning of their learning process, 2) what they achieve or fail to achieve after two years of attending the course. The conclusions may provide some implications for language teachers of mature learners as well as future directions for re-searchers of this topic.